2010
DOI: 10.1002/ijc.24995
|View full text |Cite
|
Sign up to set email alerts
|

Synergism from combined immunologic and pharmacologic inhibition of HER2 in vivo

Abstract: The monoclonal antibody trastuzumab and the EGFR/HER2 tyrosine kinase inhibitor lapatinib improve the clinical outcome of patients with HER2-overexpressing breast cancer. However, the majority of metastatic cancers will eventually progress, suggesting the need for other therapies. Because HER2 overexpression persists, we hypothesized that the anti-HER2 immune response induced by cancer vaccines would be an effective strategy for treating trastuzumab-and lapatinib-refractory tumors. Furthermore, we hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
(41 reference statements)
2
19
0
Order By: Relevance
“…Previously described 4T1-NEO and 4T1-TGFBR3 murine mammary carcinoma cell lines (H-2 d ) (22) were maintained in DMEM, 10% FBS, and 200 μg/ml G418. The 4T1-HER2 (H-2 d ) cell line was cultured as previously described (37). The 66CL4 murine mammary carcinoma cell line (H-2 d ) (gift from F. Miller, Wayne State University School of Medicine, Detroit, Michigan, USA) was cultured in DMEM, nonessential amino acids, l-glutamine, and 10% FBS (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously described 4T1-NEO and 4T1-TGFBR3 murine mammary carcinoma cell lines (H-2 d ) (22) were maintained in DMEM, 10% FBS, and 200 μg/ml G418. The 4T1-HER2 (H-2 d ) cell line was cultured as previously described (37). The 66CL4 murine mammary carcinoma cell line (H-2 d ) (gift from F. Miller, Wayne State University School of Medicine, Detroit, Michigan, USA) was cultured in DMEM, nonessential amino acids, l-glutamine, and 10% FBS (52).…”
Section: Discussionmentioning
confidence: 99%
“…For TGF-β inhibitor studies, 4T1-HER2 tumor cells were implanted into the right mammary fat pad of syngeneic female BALB/c mice (7 weeks of age), and growth was allowed to progress until tumors became palpable on day 11. Mice were either initiated on chow formulated with the type I TGF-β serine/threonine kinase inhibitor SM16 (Biogen Idec) or on regular drug-free chow (Research Diets) for 3 days, before tumor-bearing mice were vaccinated and boosted 5 days later via intradermal fat pad injection either with AdHER2ki or with AdLacZ as negative control (2.6 × 10 10 viral particles/mouse) (37,38,40). Tumor growth was monitored by caliper, and spleens were removed on day 30 after implantation for further ELISPOT analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model for HER2-positive breast cancer, the combination of lapatinib with doxorubicin resulted in enhanced tumor infiltration by IFN-g-secreting T cells than after single treatments, suggesting that lapatinib promotes a proimmunogenic response [149]. Lapatinib administered with a HER2-vaccine did not impact the immune response to immunization in both mice and HER2-overexpressing breast cancer in humans [150,151], although the presence of Tregs was not assessed in all studies [152].…”
Section: Egfr Inhibitorsmentioning
confidence: 91%
“…While it will be too early to declare these patients cured, there will be an established perception that these combinations are effectively converting a once fatal disease into one that can be controlled, possibly indefinitely. Dual PI3K/mTOR BEZ235 [171] PF-0469150 EGFR Lapatinib [149][150][151] Erlotinib [155,157] PKC AEB071 [204,212,213] Immune consequences of KIs Review informahealthcare.com Combination immunotherapy will be well on the way to being established as a mainstream effective standard of care.…”
Section: Expert Commentarymentioning
confidence: 98%
“…Very recently, Morse et al [114] demonstrated in vivo that the combination of a recombinant adenoviral vector that expresses kinase-inactive HER2 (Ad-HER2-ki) and lapatinib (an oral dual receptor tyrosine kinase inhibitor that targets both HER1 and HER2 receptors) caused significant inhibition of HER2 signaling in vitro and higher anti-tumor efficacy in vivo in a mouse model than the vaccine alone.…”
Section: Combination With Lapatinibmentioning
confidence: 99%